Conversion of algal biomass into renewable fuel: A mini review of chemical and biochemical processes - Rony, Zahidul Islam; Mofijur, M.; Hasan, M. M.; Ahmed, Shams Forruque; Badruddin, Irfan Anjum; Khan, T. M. Yunus (Frontiers in Energy Research, 2023)
In recent years, there has been a lot of interest in research on fuels that are renewable and good for the environment. This is because oil reserves are running out and fossil fuels are harmful to the planet. Microalgae could serve as a third-generation alternative to traditional feedstocks for making biofuels. Microalgae have a wide range of chemical parts, and they can be processed biochemically or thermochemically, depending on the type of strain. The products could be used to make energy or in other ways in the industrial world. Microalgae are a key resource for the next few years, and using them is important for a wide range of industrial uses. This study looks into the different ways that microalgae can be turned into different types of biofuels. This will help researchers figure out the best way to make fuel.